Collaborative Assessment and Management of Suicidality (CAMS) compared to treatment as usual (TAU) for suicidal patients: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Ryberg, Wenche; Fosse, Roar; Zahl, Per; Brorson, Inge; Møller, Paul; Landrø, Nils; Jobes, David
Abstract Background Collaborative Assessment and Management of Suicidality (CAMS) is a therapeutic framework that appears promising to reduce suicidal ideation and suicidal cognition. CAMS has not previously been evaluated in a standard specialized mental health care setting for patients with suicidal problems in general. In this pragmatic randomized controlled trial (RCT) we will investigate if CAMS is more effective than treatment as usual (TAU) in reducing suicidal thoughts and behaviors. Effects will also be investigated on mental health and symptom relief in general and upon readmissions to inpatient units. Methods/design The study is a multicenter, observer-blinded, superiority, two-armed RCT which will include patients from four clinical departments at Vestre Viken Hospital Trust, Norway. We aim to include 100 patients with moderate to strong suicidal problems, as defined by a score of 13 or more on Beck's Scale for Suicide Ideation - Current. Patients are included regardless of diagnosis. Randomization will be performed using a stratified four-block procedure with treatment unit as the stratification variable. The duration of treatment will vary depending on patients' needs and clinical assessments. Patients are interviewed by research staff at four checkpoints: baseline, 2 weeks, 6 months, and 12 months. Central outcome measures are the Beck Scale for Suicide Ideation - Current, Outcome Questionnaire – 45, and Suicide Attempt Self-Injury Count. Discussion This pragmatic trial is effectuated within the Public Health Care System in Norway, where patients have multiple problems and diagnoses and therapists have a high work load. Results from this trial are highly generalizable to a typical everyday clinical setting, and one should expect similar results if CAMS is implemented in the future as a standard component in specialized mental health care systems. Trial registration Open Science Framework: DOI10.17605/OSF.IO/JHRM2 . Registered 5 July 2015. ClinicalTrials.gov:NCT02685943 . Registered on 8 February 2016.